ADVANCED DESIGN METHODS APPLIED IN DESIGN EDUCATION AT THE UNIVERSITY OF FORESTRY - Vodenova, Pavlina (Innovation in Woodworking Industry and Engineering design, 2018)
This report will present the results achieved by Engineering Design students, Bachelor Degree during semester 6. The developed methodology is implemented in the design discipline ‘Residential Interior and Furniture Design’ at the University of Forestry in Sofia, Bulgaria, and it is a part of PhD thesis entitled “IMPLEMENTING THE SYSTEMATIC APPROACH IN CHILDREN ENVIRONMENT DESIGN FOR THE CONTEMPORARY DWELLING”. The methods used in the design class are observation and analysis of results, demonstrated by students.To make the understanding of design methodology easier and clearer, specific examples are considered. Initially, a simplified (to a certain extent) provisional design scheme is analyzed and gradually progressed to a more complex design assignment.